Trapezoidal operator preserving the expected interval and the support of fuzzy numbers - Brândaş, Adriana (Rev. Anal. Numér. Théor. Approx., 2011)
The problem to find the trapezoidal fuzzy number which preserves the expected interval and the support of a given fuzzy number is discussed. Properties of this new trapezoidal approximation operator are studied.